Análise da flambagem de paredes de alvenaria estrutural - Padilha, Tiago Montanha (2022)
This research presents analyzes of slender reinforced masonry walls built with concrete units. The analysis was performed with finite element modeling. The Abaqus computational package was used to develop the models. Slender walls are found both in buildings without a ceiling slab and in buildings with double height ceilings. The failure mode of these walls is lateral instability, also called buckling effect. Few standards allow the design of walls with high slenderness. Most standards and codes establish a certain maximum slenderness ratio value for which their methods are valid. These values have been questioned in recent scientific publications that indicate large capacity reserves in walls with slenderness close to or even greater than the maximum slenderness established in standards. The Brazilian standard establishes the slenderness ratio equal to 30 is the maximum for which the simplified method is valid for reinforced walls. The standard published in 2020, presents a more accurate method, which includes the effects of second order, to enable the design of walls with slenderness greater than 30. In addition to the formulations, the standard presents mandatory specifications. Due to the recent inclusion of this method in the Brazilian standard and the recent scientific publications, this research aims to answer: what is the accuracy of the method established in the Brazilian standard for the design of tall slender walls in structural masonry? In the parameter variation analysis, different reinforcement rates and different vertical bar positions were investigated, the compressive strength of the concrete unit equal to 8 MPa and 16 MPa and the slenderness ratio equal to 30, 40 and 50. The results indicate good agreement with the behavior of slender walls, but with imprecision regarding the stiffness of reinforced sections and with high loadings close to the critical load values. For all the models analyzed, the method resulted in significant reserves of load capacity due to the effects of geometric nonlinearity. Every wall failed due to geometric instability, indicating that the slenderness parameter equal to 30 to differentiate the buckling failure mode is adequate.